Neuroprotective Effects of Conessine in Beta-Amyloid- Induced SH-SY5Y Cells In vitro - Zhang, Dandan; Wu, Jun; Albaqami, Amirah; Mawkili, Wedad; Dayel, Faten F. Bin; Alnassfan, Tahera Waheed (Indian Journal of Pharmaceutical Education and Research, 2026)
Objectives: Alzheimer’s Disease (AD) is a brain disorder that affects the memory and thinking ability of the patient, characterised by beta-amyloid (Aβ) plaque accumulation, oxidative stress, impaired autophagy, and neuronal death, leading to cognitive decline. Current treatment for AD is limited to symptomatic relief, which highlights the demand for the discovery of newer drugs. Conessine, a steroidal alkaloid derived from Holarrhena antidysenterica, has demonstrated potential neuroprotective activity; however, its mechanism of action against beta-amyloidinduced toxicity remains unclear. Materials and Methods: In this study, we examined the protective effect of conessine on neurons in SH-SY5Y human neuroblastoma cells. MTT assay was used to study the general toxicity profile and the neuroprotective function of conessine. The level of autophagy was determined through flow cytometry analysis. The level of ROS generated in cells during beta-amyloid treatment was quantified using a fluorescence-based assay. Oxidative stress gene expression was analysed using real-time PCR experiments. Results: The results suggest that conessine at low doses (≤12.5 μg/mL) protects cells from beta-amyloid-induced cytotoxicity and restores their viability and shape. Flow cytometry showed that conessine (12.5 μg/mL) increased autophagy. In addition, DCFDA staining revealed that conessine reduced the production of Reactive Oxygen Species (ROS) induced by amyloid beta. Real-time PCR showed that conessine increased the expression of the antioxidant genes NRF2 and HMOX1 in Aβ-treated cells by 1.5 and 1.10 times, respectively, and even more in cells that were only treated with conessine (1.78 and 1.4 times). Conclusion: Collectively, these results suggest that conessine has potential as a therapeutic candidate for AD. More research is thus warranted to elucidate its molecular interactions and clinical applicability.
Keywords: Alzheimer’s Disease; Conessine; Beta-amyloid; Neuroprotection; Autophagy; Oxidative Stress; NRF2; HMOX1